Molecular and clinical features of myeloid neoplasms with somatic DDX41 mutations - Qu, Shiqiang; Li, Bing; Qin, Tiejun; Xu, Zefeng; Pan, Lijuan; Hu, Naibo; Huang, Gang; Peter Gale, Robert; Xiao, Zhijian (British journal of haematology, 2021)
Summary We screened 47 subjects with DDX41 variants among 1529 subjects with myeloid neoplasms. The most common germline variants included Splice c.935 + 4A>T, p.T360Ifs*33, p.V152G, p.S217Ifs*4, p.R311* and p.R369*. Except for the p.R369*, no other variants have been previously reported. Clinical covariates of subjects with simple DDX41 somatic variants and germline/somatic biallelic variants are similar. The two‐year overall survival (OS) of subjects with DDX41 variants was 85%. Overall response rate to demethylation therapy in subjects with DDX41 variants was 69%. The response did not correlate with the presence of a germline variant.